Multicentre cohort study ‘Rehabilitation of Occupational Skin Diseases - Optimization and Quality Assurance of Inpatient Management (ROQ)’: results from a 3-year follow-up - Brans, Richard; Skudlik, Christoph; Weisshaar, Elke; Scheidt, Reginald; Ofenloch, Robert; Elsner, Peter; Wulfhorst, Britta; Schönfeld, Michael; John, Swen Malte; Diepgen, Thomas L. (Contact dermatitis, 2016)
Background A tertiary individual prevention programme (TIP) is offered to patients with severe occupational skin disease (OSD) in Germany. Previously, it was shown that the burden of OSDs is considerably reduced in patients up to 1 year after the TIP. Objectives To evaluate the long-term effects of the TIP. Patients and methods In a prospective multicentre cohort study, the clinical and patient-reported outcome data 3 years after the TIP were evaluated. Results Of the 1788 patients initially included in the study, 1410 were available for the 3-year follow-up analysis. The severity of OSD, the use of topical corticosteroids and days of absence from work were significantly reduced 3 years after the TIP, and the quality of life and skin protective behaviour were significantly improved. Of the patients, 96.9% were able to resume work. One thousand one hundred and sixty-six patients (82.7%) were still working 3 years after the TIP, 874 of them (75.0%) in the same occupational field. Hairdressers had the lowest rate of remaining in their original profession (41.3%). Conclusions The follow-up during 3 years of this unique cohort of patients with OSDs shows that the TIP is associated with sustained improvements in terms of disease severity, ability to work, quality of life, and prognosis.
Gesehen am 18.05.2020